2012
DOI: 10.1021/ja210528v
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemical Proteomics Approach To Identify Post-translational Modification-Mediated Protein–Protein Interactions

Abstract: Post-translational modifications (PTMs) (e.g. acetylation, methylation, and phosphorylation) play crucial roles in regulating the diverse protein-protein interactions involved in essentially every cellular process. While significant progress has been made to detect PTMs, profiling protein-protein interactions mediated by these PTMs remains a challenge. Here, we report a method that combines a photo-cross-linking strategy with stable isotope labeling in cell culture (SILAC)-based quantitative mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
108
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 23 publications
3
108
0
Order By: Relevance
“…S5B). The MORC3 CW domain exhibited a significant preference for H3K4me2 and H3K4me3 over H3K4me0, consistent with previous reports of human MORC3 binding preferences (12,13). We used isothermal titration calorimetry (ITC) to calculate the binding affinity of the MORC3 CW domain for both unmodified H3K4me0 and H3K4me3 H3 peptides (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…S5B). The MORC3 CW domain exhibited a significant preference for H3K4me2 and H3K4me3 over H3K4me0, consistent with previous reports of human MORC3 binding preferences (12,13). We used isothermal titration calorimetry (ITC) to calculate the binding affinity of the MORC3 CW domain for both unmodified H3K4me0 and H3K4me3 H3 peptides (Fig.…”
Section: Resultssupporting
confidence: 82%
“…1A). The CW-type zinc finger has been identified as an H3K4me reader module as assayed by structural and biochemical methods (11)(12)(13)15). To gain insight into the molecular mechanism of MORC3, we solved the crystal structure of the MORC3 ATPase-CW domain cassette in complex with the nonhydrolyzable ATP analog AMPPNP and H3(1-15)K4me3 peptide by singlewavelength anomalous diffraction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that the CW domains of ZCWPW1 (8), MORC3 (10), and MORC4 (9) are readers of H3K4 3 methylated histones with differing preferences for histone H3K4 methylation states (i.e. ZCWPW1 and MORC3 preferentially recognize histone H3K4me3 (8,10), whereas the CW domain of human MORC4 prefers dimethylated H3K4 (9)). The LSD2 CW domain is required for the demethylation function of LSD2 but does not bind to any H3K4 peptides (13).…”
mentioning
confidence: 99%